Gendered perspectives on reproduction and sexuality - Segal, Marcia Texler, 1940-; Demos, Vasilikie P.; Kronenfeld, Jennie J. (Advances in gender research, 2004)
This volume offers feminist perspectives on the social, cultural and medical aspects of women as sexual beings and of their fertility, pregnancy and child bearing. It serves as a companion to "Advances in Gender Research volume 7, Gender perspectives on Health and Medicine: Key Themes". As in the previous volume, the authors critique and transcend conventional biomedical approaches to the subject matter. The seven essays raise questions about control and agency asking who decides if, when and how fertility should be controlled and the circumstances under which child birth takes place. They address decision-making on multiple levels from the individual to the national and transnational and grapple with such controversial matters as genital cutting, self-help menstrual extraction and direct-entry midwifery. They interrogate the policies and practices of states and transnational agencies that have a bearing on sexuality and reproductive health, the ways in which womens genitalia have been objectified and manipulated by practices that purport to be both traditional and modern, and the motivations of those who provide alternative forms of fertility control and birthing methods. The intended audience is the social science community, especially those who are interested in the study of gender, sexuality and reproductive health, medicine and alternative medicine, and the areas where these interface.